1990
DOI: 10.1111/j.1399-3054.1990.tb04403.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between activated charcoal, Fe‐EDTA and other organic media ingredients in cultured anthers of Anemone canadensis

Abstract: The effects of activated charcoal and organic substances on embryogenesis in anther cultures of Anemone canadensis L. were studied. Embryogenesis was independent of the presence in the culture medium of glycine, nicotinic acid, pyridoxine, thiamine, folic acid, d‐biotin or myoinositol. Absence of Fe‐EDTA totally inhibited embryogenesis. Activated charcoal (AC) adsorbed Fe‐EDTA, pyridoxine, folic acid and nicotinic acid in a double‐layer medium almost completely within 24 h. If petri dishes according to the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The present study also showed that embryo formation in the anthers of H. nobilis was stimulated on media containing AC which has frequently been used for anther culture in many plant species due to its ability to absorb some inhibiting substances such as polyphenols, ethylene (Horner et al, 1977;Kohlenbach and Wernicke, 1978;Johansson, 1983;Mensuali-Sodi et al, 1993;DolcetSanjuan et al, 1997) and abscisic acid (Johansson et al, 1982(Johansson et al, , 1990. On the other hand, AC also absorbs nutrients, such as thiamine, nicotinic acid (Weatherhead et al, 1979) and Fe-EDTA (Heberle-Bors, 1980), as well as plant growth regulators such as NAA and cytokinin (Weatherhead et al, 1978).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The present study also showed that embryo formation in the anthers of H. nobilis was stimulated on media containing AC which has frequently been used for anther culture in many plant species due to its ability to absorb some inhibiting substances such as polyphenols, ethylene (Horner et al, 1977;Kohlenbach and Wernicke, 1978;Johansson, 1983;Mensuali-Sodi et al, 1993;DolcetSanjuan et al, 1997) and abscisic acid (Johansson et al, 1982(Johansson et al, , 1990. On the other hand, AC also absorbs nutrients, such as thiamine, nicotinic acid (Weatherhead et al, 1979) and Fe-EDTA (Heberle-Bors, 1980), as well as plant growth regulators such as NAA and cytokinin (Weatherhead et al, 1978).…”
Section: Discussionmentioning
confidence: 56%
“…To date, there have been no reports on haploid plant production of H. nobilis, although embryogenesis from anther cultures has been reported (Georgiev and Chavdarov, 1974). Furthermore, indications are that embryo formation from anther cultures was improved by supplementing activated charcoal (AC) into medium, using the double-layer culture method in two Ranunculaceae species, Anemone and Clematis (Johansson et al, 1982(Johansson et al, , 1990Johansson, 1983). Our efforts were aimed at producing haploid plants of H. nobilis by anther culture.…”
Section: Introductionmentioning
confidence: 99%
“…Known primarily for its use in the purification of water (Baudu et al, 1993;Crittenden et al, 1993), hypotheses on the mode of action for AC generally relate to the adsorptive properties of AC in tissue culture medium (Fridborg et al, 1978;Ebert and Taylor, 1990;Johannson et al, 1990;Pullman and Gupta, 1991;Ebert et al, 1993;Van Winkle and Pullman, 2003;Van Winkle et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The effect of AC on growth regulator uptake is still unclear. Johansson and Eriksson (1977) and Johansson et al (1990) suggested that AC may gradually release certain adsorbed products, such as nutrients and growth regulators, which become available to plants.…”
Section: Introductionmentioning
confidence: 98%